2010
DOI: 10.1523/jneurosci.6251-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

Brain-Derived Neurotrophic Factor Is Associated with Age-Related Decline in Hippocampal Volume

Abstract: Hippocampal volume shrinks in late adulthood, but the neuromolecular factors that trigger hippocampal decay in aging humans remains a matter of speculation. In rodents, brain-derived neurotrophic factor (BDNF) promotes the growth and proliferation of cells in the hippocampus and is important in long-term potentiation and memory formation. In humans, circulating levels of BDNF decline with advancing age, and a genetic polymorphism for BDNF has been related to gray matter volume loss in old age. In this study, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
364
8
8

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 504 publications
(403 citation statements)
references
References 70 publications
(92 reference statements)
23
364
8
8
Order By: Relevance
“…This could well be related to an age-related decrease in sBDNF levels. In our sample, the mean sBDNF level was 18.27 ng/ml, which is in line with earlier reports of elderly populations (Erickson et al, 2010;Bus et al, 2012;Rapinesi et al, 2015) but lower compared with levels ranging from 9.5 to 29.0 μg/ml in non-elderly depressed patients (Sen et al, 2008). Differences in the sBDNF level could also be explained by sample characteristics and protocols used (eg, urbanicity, sex, smoking status, time of blood withdrawal, and so on; Bus et al, 2011).…”
Section: Relationship Between Clinical Response and Sbdnfsupporting
confidence: 92%
See 2 more Smart Citations
“…This could well be related to an age-related decrease in sBDNF levels. In our sample, the mean sBDNF level was 18.27 ng/ml, which is in line with earlier reports of elderly populations (Erickson et al, 2010;Bus et al, 2012;Rapinesi et al, 2015) but lower compared with levels ranging from 9.5 to 29.0 μg/ml in non-elderly depressed patients (Sen et al, 2008). Differences in the sBDNF level could also be explained by sample characteristics and protocols used (eg, urbanicity, sex, smoking status, time of blood withdrawal, and so on; Bus et al, 2011).…”
Section: Relationship Between Clinical Response and Sbdnfsupporting
confidence: 92%
“…At baseline, higher sBDNF levels were associated with larger hippocampi, a result that was also shown by Erickson et al (2010) in 142 older adults without dementia and without depression.…”
Section: Relationship Between Hippocampal Volume Changes and Sbdnf Chmentioning
confidence: 53%
See 1 more Smart Citation
“…*P < 0.05 vs. WT controls; # P < 0.05 vs. other hippocampal layers stages of AD (Peng et al 2005). Recent studies revealed that BDNF is associated with age-related decline in hippocampal volume (Erickson et al 2010) and prevents hippocampal atrophy in APP/PS1 mice Fig. 6 Analyses of amyloid plaque load and expression of Aβ metabolism enzymes in the hippocampus.…”
Section: Resultsmentioning
confidence: 98%
“…Researchers suggested that aging might enhance basal norepinephrine level and depress heart rate variability (Shimazu et al 2005;Reardon and Malik 1996;Jensen-Ustad et al 1997). Brain-derived neurotropic factor (BDNF), a potent marker of adult neurogenesis and cognitive performance, declines with aging (Erickson et al 2010). Age-related changes in levels of cortisol, adrenocorticotropic hormone, dehydroepiandrosterone (DHEA) and of its sulfate (DHEAS), serotonin, and dopamine have been reported in literatures (Kuzina et al 2010;Garau et al 2006 andYonezawa et al 1989;Dreher et al 2008).…”
Section: Introductionmentioning
confidence: 99%